Pulmonary Embolization in the Dog: Its Effects on Blood Coagulation and on Pulmonary Artery Pressures - Hampton, James W.; Jaques, William E.; Bird, Robert M.; Selby, David M. (Thrombosis and Haemostasis, 1961)
1. Infusions containing particulate matter, viz. whole amniotic fluid, amniotic fluid sediment, and glass beads, produce in dogs changes in both early and late phases of the clotting reaction. These changes are associated with the development of pulmonary hypertension.2. When dogs were given an active fibrinolysin followed by an infusion of whole amniotic fluid, the alterations in the clotting mechanism were either delayed or did not appear. No pulmonary hypertension developed in these animals.3. We infer that infusions containing particulate matter will produce in dogs both pulmonary hypertension and changes in the clotting mechanism. Although these are independent changes, both are as closely related to the damage to the pulmonary vessels as they are to the biological nature of the infusions.